A little relief: Ecological functions and autogenesis of wetland microtopography. (3rd December 2020) - Diamond, Jacob S.; Epstein, Joshua M.; Cohen, Matthew J.; McLaughlin, Daniel L.; Hsueh, Yu‐Hsin; Keim, Richard F.; Duberstein, Jamie A.
Abstract: Microtopography, or the small‐scale variation in ground surface height (10 −1 –10 0  m) over short (10 0 –10 2  m) spatial scales, is a ubiquitous feature of wetlands globally. This variation in elevation, characterized by local high ("hummocks") and low ("hollows") patches, is more structured than what is observed in uplands, and is intertwined with concordantly structured spatiotemporal variability in hydrologic regimes and associated ecological processes. The importance of microtopography in wetlands is manifold, with critical influence on local hydrological, biogeochemical, and biological processes. Further, the creation and maintenance of wetland microtopography is a balance between activation processes (i.e., those that induce random elevation variation) and autogenic reinforcement processes (i.e., those that provide the feedbacks necessary for the persistence of microtopography). While there are many mechanisms that create vertical structure (e.g., tree falls, accumulation of roots and soil organic matter, and sediment deposition), they all yield a similar core feedback to enhance and sustain microtopographic structure. Finally, microtopography contributes to spatial patterning that confers emergent ecosystem‐scale functions such as hydrologic storage and flows, carbon cycling, organism dispersal, and biodiversity. There is an ongoing need to study the origins and implications of this fine‐scale variation in elevation, as well as the utility of including microtopography in model predictions and ecological restoration efforts. This article is categorized under: Water and Life > Conservation, Management, and Awareness Abstract : In wetlands, a little relief or microtopographic variation in the soil surface influences numerous hydrological and biogeochemical processes, creating strong feedbacks with ecological patterns, and functions that are important for management and conservation.